Perbedaan Peningkatan Prestasi Belajar IPA Melalui Pembelajaran Berbasis Masalah dan Inkuiri Terbimbing Pokok Bahasan Energi dan Daya Listrik Kelas IX di SMPN 20 Bandar Lampung - Tsamaniariaty Hidayah; Sulton Djasmi; Undang Rosidin (Universitas Mathla'ul Anwar Banten, 2018)
DIFFERENCES IN INCREASED ACHIEVEMENT OF SCIENCE LEARNING THROUGH PROBLEM BASED AND INQUIRY LEARNING GUIDED PRINCIPLES OF ENERGY AND POWER AT GRADE IX OF SMPN 20 BANDAR LAMPUNG. Difference Improving Learning Achievement of Science Through Learning Based On Problem And Discussion Guided Inquiry Energy And Power Supply Of Ninth Grade At Smpn 20 Bandar Lampung. The research aims to know : (1) difference in improving pre-test and post-test of cognitive in learning based of problem. (2) difference in improving pre-test and post-test of cognitive in learning guided inquiry. (3) difference in improving student's post-test of cognitive in learning based of problem and guided inquiry. This research is an experimental research by